2023
DOI: 10.3389/fphy.2023.1130225
|View full text |Cite
|
Sign up to set email alerts
|

Scaling laws of out-of-time-order correlators in a non-Hermitian kicked rotor model

Abstract: We investigate the dynamics of the out-of-time-order correlators (OTOCs) via a non-Hermitian extension of the quantum kicked rotor model, where the kicking potential satisfies PT-symmetry. The spontaneous PT-symmetry breaking emerges when the strength of the imaginary part of the kicking potential exceeds a threshold value. We find, both analytically and numerically, that in the broken phase of PT symmetry, the OTOCs rapidly saturate with time evolution. Interestingly, the late-time saturation value scales as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…The dynamics of OTOCs, originally introduced by Lakin et al, in the study of quasiclassical theory of superconductivity [46], has received extensive studies in the fields of high energy physics [47][48][49], condensed matter physics [50][51][52][53][54][55] and quantum information [56][57][58]. It has been found that OTOCs can effectively detect quantum chaos [59][60][61][62], quantum thermalization [63], and information scrambling [64][65][66][67][68][69]. In the semiclassical limit, the exponential growth of OTOCs is governed by the Lyapunov exponent of classical chaos, which demonstrates a route of quantum-classical correspondence [70].…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of OTOCs, originally introduced by Lakin et al, in the study of quasiclassical theory of superconductivity [46], has received extensive studies in the fields of high energy physics [47][48][49], condensed matter physics [50][51][52][53][54][55] and quantum information [56][57][58]. It has been found that OTOCs can effectively detect quantum chaos [59][60][61][62], quantum thermalization [63], and information scrambling [64][65][66][67][68][69]. In the semiclassical limit, the exponential growth of OTOCs is governed by the Lyapunov exponent of classical chaos, which demonstrates a route of quantum-classical correspondence [70].…”
Section: Introductionmentioning
confidence: 99%